IN VITRO ANTI-INFLAMMATORY ACTIVITY OF QUERCITRIN ISOLATED FROM ALLAMANDA CATHARTICA LINN - K.HEMA (International Journal of Pharma and Bio Sciences, 2014)
In the present work, the flavonoid quercitrin obtained from the fresh flowers of Allamanda Cathartica Linn. was evaluated for anti-inflammatory activity by in vitro hemolytic membrane stabilizing study. The effect of inflammation condition was studied on erythrocyte exposed to hypotonic solution. The results of the evaluation indicate that the obtained compound was found to show membrane stabilizing activity, which was optimum at 75µg.